Creatinine-modified Child-Turcotte-Pugh score is a good predictor of a short-term survival in patients with bleeding from esophageal varices - Radisavljević, Mirjana Miodrag; Bjelaković, Goran; Jović, Jasna; Radovanović Dinić, Biljana; Benedeto Stojanov, Danijela; Brzački, Vesna; Marković Živković, Bojana (Vojnosanitetski pregled, 2017)
Background/Aim. Bleeding from esophageal varices is a significant factor in mortality of patients with terminal liver cirrhosis. This complication is a major health problem for recipients on the list for liver transplant. In that regard, studying predictors of variceal bleeding episode is very importatnt. Also, it is important to find the best survival predictor among prognostic scores. The aim of the study was to compare validity of prognostic scores in assessment of survival in hospital-treated patients after bleeding from esophageal varices, and to compare validity of baseline Child-Turcotte-Pugh (CTP) and Modul for End-stage Liver Disease (MELD) scores with CTP creatinine modified (CTP-crea) I and II scores in assessment of survival in patients within a long-term follow-up period after the episode of bleeding from esophageal varices. Methods. The study included a total of 126 patients suffering from terminal liver cirrhosis submited to testing CTP score score I and II, MELD score, MELD Na score, integrated MELD score, MELD sodium (MESO) index, United Kingdom Model for End-Stage Liver Disease (UKELD) score and updated MELD score. Results. Patients with bleeding from esophageal varices most often had CTP score rank C (46,9%). CTP score rank B had 37.5% patients, while the smallest percentage of patients had CTP rank A, 15.6% of them. Patients who have values of CTP score higher than 10.50 and bleeding from esophagus, have 3.2 times higher chance for death outcome compared to other patients. Patients who have values of CTP-crea I score higher than 10.50 and bleeding from esophagus, have 3.1 times higher chance for death outcome than other patients. Patients who have values of CTP-crea II score higher than 11.50 and bleeding from esophagus, have 3,7 times higher chance for death outcome compared to other patients. Conclusion. Survival of patients with bleeding from esophageal varices in the short-term follow up can be predicted by following CTP score and creatinine modified CTP scores. Patients with bleeding from esophageal varices who have CTP score and CTP-crea I score higher than 10.5 and CTP-crea II score higher than 11.5, have statistically significantly higher risk from mortality within one-month follow-up compared to patients with bleeding from esophageal varices who have lower numerical values of scores of the CTP group
Keywords: liver cirrhosis; esophageal and gastric varices; hemorrhage; prognosis